Scarves - Albrechtsen, Nicky (New York, NY : Thames & Hudson, 2011)
Styles of the eras ## Artists' scarves ## Textile designers ## The great scarf companies##The designer scarf ## Historic scarves ## The travel scarf ## Scarves and advertising ## Collectables.
boek